Deconstructing leisure time and workload: case of women bean producers in Kenya - Nchanji, Eileen Bogweh; Mutua, Mercy M.; Odhiambo, Collins; Nchanji, Yvonne Kiki; Karanja, David (Springer, 2021)
Background: The notion of leisure became pronounced more than 20 years ago when women who worked on or out of the farm came home to a “second shift,” which entailed domestic work and childcare. This gap continues today not only between men and women but also among women and men. Women’s challenges in terms of their leisure arise out of or are shaped by social norms and diferent life contexts. Method: The Women’s Empowerment in Agriculture Index (WEAI) was conducted to understand women’s empowerment and disempowerment status in agricultural activities in five counties in Kenya in 2017. In 2019, focus group discussions were carried out in two of the fve counties to understand how men and women farmers define leisure and assess the leisure gap and its effect on women’s farm and household activities. We were also interested in understanding how men’s and women’s workload affects leisure and other productive economic activities, resulting in empowerment and how women’s unpaid work contributes to income poverty. Result: The WEAI showed that 28% of disempowerment (5DE) in women farmers is due to lack of time for leisure activities and 18% from being overworked. This means that the time indicator accounts for 46% of disempowerment in Kenyan women bean farmers. Men in Bomet and Narok spent more time than women in raising large livestock and leisure. Women in Bomet spent more time than men in cooking and domestic work (fetching water and collecting fuelwood), while men in Bomet spent more time than women in managing their businesses. Conclusion: Work overload is a constraining factor to women’s empowerment in bean production and agricultural productivity. What is considered leisure for men and women is embedded in society’s social fabrics, and it is contextual. This paper highlights instances where leisure provides a way for women to embody and/or resist the discourses of gender roles in the bean value chain and households to enhance food security and health.